Patterns of palatal rugae as an indicator of identification in young adults of Nepal - Shrestha, Ashish; Shrestha, Sushmita; Marla, Vinay; Agrawal, Navin (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The current study was conducted to identify and determine the association between gender and characteristics of palatal rugae in Nepalese population. Materials & Methods: Characteristics of palatal rugae including number, length, shape, direction and unification were analyzed in 100 maxillary dental plaster casts. Association between palatal rugae and gender were tested using chi square analysis and statistical descriptors were identified using SPSS 10.0 keeping the level of statistical significance at p<0.05. Results: A total of 997 rugae were traced. Females were found to have more rugae than males though statistically not significant. In the present study significant difference in secondary (p=0.012), fragmentary (p=0.005), straight (p=0.001) and perpendicular directed (p<0.0001) palatal rugae were observed, which were higher among females. Forward directed followed by backward were predominantly observed and more among females. Wavy followed by curved, straight and circular rugae was the most prevalent shape. Conclusion: No two individual had similar rugae pattern. They can be used to identify people and differentiate between males and females in addition to other tools of identification and has great application in forensic science.